Quiet Quitting Among Nurses: A Case Study in a Northern Italian Hospital - Sara Rinaldi; Ester Pomarolli (Nursing Reports)
Background/Objectives: Quiet Quitting (QQ) describes a state of reduced workplace engagement characterized by a lack of motivation and initiative. Employees practicing QQ typically limit their efforts to fulfilling only their assigned tasks, expending the minimum necessary energy, while still ensuring the completion of their core responsibilities. QQ is an emerging phenomenon in healthcare settings following the COVID-19 pandemic and is still relatively unexplored in the literature. The aim of this study is to assess QQ among nurses in a northern Italian hospital. Methods: A cross-sectional study with a convenience sample of 91 nurses in a single-specialist orthopedic hospital was conducted. Data were collected in August 2024 using an online form of the Quiet Quitting Scale (QQS). Demographic data were collected, including gender, age, years of work experience and department. Results: A response rate of 83.50% was recorded. Data analysis revealed that 46.06% of the sample (35 nurses) was identified as quiet quitters. Fewer years of service and a younger age were associated with a higher probability of Quiet Quitting. The highest average score was observed for “Lack of motivation” subscale at 2.40 (SD = 1.14). Conclusions: The findings establish QQ as a significant issue requiring urgent attention in healthcare. To guarantee high-quality nursing care, healthcare organizations must prioritize interventions focused on enhancing employee support and work environment. Longitudinal research is necessary to explore the long-term effects of QQ on patient outcomes and to evaluate the success of targeted interventions.